Legal Protection of Anesthesia Technicians for Anesthesia Procedures Without an Anesthesiologist in Hospitals - Afriansyah, Afriansyah; Hayatuddin, Khalisah; Martini, Martini (Journal of Law, Politic and Humanities, 2025)
This study aims to analyze the authority and forms of legal protection for anesthesia technicians in performing anesthesia procedures without the presence of an anesthesiologist in hospitals. The research method used is normative legal research with statutory and conceptual approaches, using primary, secondary, and tertiary legal materials analyzed qualitatively. The research results show that there is a gap between normative provisions in Minister of Health Regulation No. 18 of 2016 and empirical practice in the field. Although the regulation governs the delegation of authority (delegation and mandate) for anesthesia technicians under certain conditions, its implementation still faces limitations in supervision and unclear legal responsibility. Law No. 17 of 2023 on Health brings important changes by positioning anesthesia technicians as medical technical personnel and making competency standards the basis of authority, while providing legal protection for health workers who act to save patients' lives in emergency situations. However, legal protection for anesthesia technicians who perform elective procedures without an anesthesiologist remains weak as it may be considered exceeding authority. In conclusion, legal protection for anesthesia technicians in anesthesia procedures without an anesthesiologist is limited and contextual: strong in emergency situations, but weak in elective procedures. More explicit legal arrangements adaptive to health service conditions in regions are needed to provide proportional legal certainty and protection for anesthesia technicians and ensure patient safety.